2017
DOI: 10.1186/s13036-017-0086-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of starch-chitosan-gelatin foams and the impact of gelatin on MC3T3 mouse osteoblast cell viability

Abstract: BackgroundThis study examines the effects of adding gelatin to a starch-chitosan composite foam, focusing on the altered structural and biological properties. The compressive modulus of foams containing different gelatin concentrations was tested in dry, wet, and lyophilized states. MC3T3 mouse osteoblast cells were used to test the composite’s ability to support cell growth. The stability of the foams in α-MEM culture media with and without cells was also examined.ResultsIt was found that for dry foams, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…The incorporation of gelatin in other polymers is one of the strategies to improve their biological activity. For instance, Risser et al () showed that increasing concentration of gelatin in starch‐chitosan‐gelatin composite foams have a positive effect on the growth and proliferation of MC3T3 mouse osteoblast cells. In turn, the incorporation of gelatin in PVA electrospun nanofibers significantly improved the adhesion, spreading, and flattening of the 3T3 mouse fibroblasts (Huang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of gelatin in other polymers is one of the strategies to improve their biological activity. For instance, Risser et al () showed that increasing concentration of gelatin in starch‐chitosan‐gelatin composite foams have a positive effect on the growth and proliferation of MC3T3 mouse osteoblast cells. In turn, the incorporation of gelatin in PVA electrospun nanofibers significantly improved the adhesion, spreading, and flattening of the 3T3 mouse fibroblasts (Huang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome its limitations including high degradation rate in aqueous environment and weak mechanical properties, chemical crosslinking agents, such as formaldehyde, glyoxal, glutaraldehyde, genipin, and transglutaminase, are used (Pulat & Akalin, ; Xing et al, ). Since, gelatin contains Arg‐Gly‐Asp (RGD) sequences that promote cell adhesion and spreading, it has been blended with other polymers (e.g., chitosan, alginate, poly(vinyl alcohol) ‐ PVA, and starch/chitosan) to obtain hydrogels with improved biological activity (Huang, Hu, & Wei, ; Maji, Dasgupta, Pramanik, & Bissoyi, ; Risser, Banik, Brown, & Catchmark, ; Sarker et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Com isso, a eficácia dessa blenda foi estudada por diversos pesquisadores, comoCovarrubias et al, (2018), que desenvolveram um scaffold com quitosana e gelatina contendo nanopartículas de biovidro, o que resultou em um biomaterial com capacidade de acelerar a recuperação óssea. Assim comoRisser et al, (2017), que analisaram o efeito biológico de uma espuma de amido e quitosana com gelatina, em células osteoblásticas, e observaram um crescimento e proliferação celular proporcional à concentração de gelatina na amostra.Dessa forma, a blenda de quitosana e gelatina apresenta algumas vantagens, como aumento na permeação ao vapor, potencializa as propriedades que influenciam a atividade biológica, como melhora da biocompatibilidade, presença de aminoácidos que promovem adesão e migração celular, pois tanto a quitosana como a gelatina influenciam o meio celular…”
unclassified